2011
DOI: 10.1016/j.jim.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A broadly applicable approach to T cell epitope identification: Application to improving tumor associated epitopes and identifying epitopes in complex pathogens

Abstract: Epitopes are a hallmark of the antigen specific immune response. The identification and characterization of epitopes is essential for modern immunologic studies, from investigating cellular responses against tumors to understanding host/pathogen interactions especially in the case of bacteria with intracellular residence. Here, we have utilized a novel approach to identify T cell epitopes exploiting the exquisite ability of particulate antigens, in the form of beads, to deliver exogenous antigen to both MHC cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…We observed that i Ft -MHB induces higher levels of the pro-inflammatory cytokines [IL-1β (Figure 10A), IL-6 (Figure 10C), and TNF-α (Figure 10D)], as compared to i Ft -BHI, while both immunogens induced similar levels of IL-10. Finally, we investigated the presentation of i Ft -MHB versus i Ft -BHI using an Ft- specific T cell hybridoma (FT25 6D10), which is specific to an epitope corresponding to Ft 50 s-ribosomal protein (20) and secretes IL-5 on engagement with cognate major histocompatibility complex (MHC)-peptide complex (13). Co-cultures of FT25 6D10 and APCs (PECs or BMDCs) exposed to i Ft -MHB exhibited higher levels of IL-5 compared to that of i Ft -BHI (Figure 11).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that i Ft -MHB induces higher levels of the pro-inflammatory cytokines [IL-1β (Figure 10A), IL-6 (Figure 10C), and TNF-α (Figure 10D)], as compared to i Ft -BHI, while both immunogens induced similar levels of IL-10. Finally, we investigated the presentation of i Ft -MHB versus i Ft -BHI using an Ft- specific T cell hybridoma (FT25 6D10), which is specific to an epitope corresponding to Ft 50 s-ribosomal protein (20) and secretes IL-5 on engagement with cognate major histocompatibility complex (MHC)-peptide complex (13). Co-cultures of FT25 6D10 and APCs (PECs or BMDCs) exposed to i Ft -MHB exhibited higher levels of IL-5 compared to that of i Ft -BHI (Figure 11).…”
Section: Resultsmentioning
confidence: 99%
“…Examples of those techniques include screening of retrovirus-based cDNA libraries (Wang et al, 1998; Aoshi et al, 2005), use of random expression genomic libraries in E. coli to feed macrophages as APCs (Gonçalves et al, 2006), screening of purified proteins (from a genomic library) coupled to beads (Valentino et al, 2011a,b), screening of synthetic minigene libraries (Hondowicz et al, 2012), and screening of plasmid-encoded combinatorial peptide libraries (Siewert et al, 2012). …”
Section: Modern Vaccinology Concepts Applied To Scrub Typhusmentioning
confidence: 99%
“…For example, Turner and colleagues developed a bead capture system using polyhistidine tag [90,91]. This method has recently been demonstrated to have utility for T-cell antigen discovery using a small (45 ORF) Francisella tularensis expression library [92,93]. HT T-cell screening of proteomes is a new field, and similar studies are in the pipeline.…”
Section: Orfeome Expression Librariesmentioning
confidence: 99%